Optic Nerve Sheath Diameter Cutoff Point for Detection of Increased Intracranial Pressure in the Emergency Department - Ussahgij, Wanatchaporn; Toonpirom, Wipada; Munkong, Waranon; Lenghong, Kamonwon; Apiratwarakul, Korakot (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Ultrasound of the optic nerve sheath diameter (ONSD) is one of the most widely used noninvasive methods of screening for high intracranial pressure. AIM: This study aimed to measure the ONSD and to find the appropriate cutoff point to indicate increased intracranial pressure. METHODS: We examined 93 participants over 18 years of age with abnormal neurologic signs or symptoms and took computerized tomography (CT) scans of their brains. We measured the ONSD through ultrasound with the head positioned at 30°. We also used a linear array probe to measure the ONSD in the position after connecting the eyeball 3 mm. RESULTS: The average of the ONSD at each side was 4.76 mm (95% confidence interval [CI]: 4.65–4.87) in the normal CT scan group and 5.33 mm (95% CI: 5.13–5.33) in the abnormal CT scan (indicating high intracranial pressure) group. An ONSD cutoff point of 5.0 mm yielded 74.14% sensitivity and 49.22% specificity. The positive predictive value was 0.38 and negative predictive value was 0.82. CONCLUSION: The ONSD in the abnormal CT scan group was greater than in the normal CT scan group, and an ONSD of 5.0 mm can be used as a cutoff point for detecting increased intracranial pressure.